EFFORTS TO IMPROVE STUDENTS' LEARNING MOTIVATION IN ISLAMIC EDUCATION SUBJECT THROUGH PAIKEM-BASED LEARNING STRATEGIES TYPE EVERYONE IS A TEACHER HERE IN STUDENTS GRADE VIII-1 OF SMPN 1 SUMENEP 2016/2017 - Rohmatun, Anis (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2021)
The results of observation directly in grade VIII-1 through pre-cycle action research can be known the method used by teachers in the field of study Islamic education subject (PAI) who have not fully prioritized active learning and tend to occur one-way communication means that learners tend to be passive in learning this can be seen from readiness and activeness at the time of learning, it is also seen by the existence of learning results that have not been maximized meaning that they have not reached the minimum completeness criteria (KKM). Readiness in learning and activeness of learners illustrate the spirit to follow the learning. This research uses action research in students of grade VIII-1 SMP Negeri 1 Sumenep. The object of this research is in class VIII-1 SMP Negeri 1 Sumenep. In this study, researchers used one class to implement PAIKEM-based learning strategies of Everyone Is A Teacher Here, namely class VIII-1 with 33 students. After the action is carried out through PAIKEM-based learning strategies Everyone Is A Teacher Here by creating an active learning atmosphere then the atmosphere of the class becomes alive, learners become the spirit of learning and maximum learning outcomes. This research was conducted in three stages, namely pre-cycle stage, cycle 1 and cycle 2. At the pre-cycle stage of learning motivation learners had a percentage of 58.57% and an average final test of 64. In cycle 1 after the implementation of learning motivation measures learners increased to 68.57% and the average final test was 74. While in the 2nd cycle after the evaluation of the implementation of actions in the 2nd cycle learning motivation has increased, namely the learning motivation of learners can be percentaged to 80.00% and the average final test of learners is 79. The results of research conducted by researchers prove that there is an increase in learning motivation that has an impact on the learning outcomes of learners in following Islamic education subject (PAI) learning through PAIKEM-based learning strategies of Everyone Is A Teacher Here. This motivation can be seen from the activeness and readiness of learners in following the learning. Learning takes place with a high spirit of learning from learners so that learning can run effectively.